Lamotrigine Enhances Autophagy and Reduces Post-Traumatic Spinal Neural Injury in Mice - Mengting Zhang; Li Chen; Heren Gao; Tao Liu (Journal of Integrative Neuroscience)
Background: Lamotrigine (LTG) is an antiepileptic drug that stabilizes the presynaptic membrane by blocking sodium channels and inhibiting excessive glutamate release. Its neuroprotective effects have been demonstrated in various pathological states. However, the role of LTG in spinal cord injury (SCI) and its relationship with autophagy, which is essential for cellular homeostasis, warrant further investigation. Methods: We established a mouse model of SCI using complete spinal transection. The neuroprotective effects of LTG were assessed using immunostaining and functional assessments, including Basso Mouse Scale (BMS) scores, lesion site area, and synapse survival. Western blot analyses were also performed to further examine the underlying cellular and molecular mechanisms of autophagy. Results: LTG treatment promoted the post-traumatic survival of spinal neurons, improved BMS scores, reduced lesion site area, and enhanced synapse survival in a mouse model of SCI. Furthermore, LTG attenuated apoptosis following SCI by activating autophagy during the secondary injury phase. These findings indicate that LTG-enhanced autophagosome formation and autolysosome degradation play a key role in reducing neuronal loss after SCI. Conclusion: LTG appears to attenuate post-traumatic spinal neural injury by enhancing autophagy flux.